Non-pharmaceutical hypercholesterolemia management by plant stanol-enriched product consumption - N. V. Perova (Кардиоваскулярная терапия и профилактика)
Phytosterols and phytostanols are plant analogs of cholesterol, inhibiting cholesterol (XCH) absorption by intestine epithelium and, therefore, decreasing CH blood levels. Sterols and especially stanols are absorbed in the intestine to a much lesser extent than CH, and their plasma concentrations are also less than those of CH. It is known that rare cases of hypercholesterolemia, e.g., genetic hypersitosterolemia, are linked to increased coronary heart disease risk. For stanols, there is no evidence of such a risk. Development of lipid-dissolving stanol esters provided an opportunity to enrich various foods (spreads, yogurts, milk, etc.; trade mark Benecol, Raisio Company, Finland) with physiological stanol ester doses (1,5-2,0 g/d). Stanol consumption results in CH and low-density lipoprotein CH level decrease by 10-15%, in addition to low-lipid diet effects, and therefore could be used for prevention and treatment of atherogenic hypercholesterolemia.